Sox6 Up-Regulation by Macrophage Migration Inhibitory Factor Promotes Survival and Maintenance of Mouse Neural Stem/Progenitor Cells - Ohta, Shigeki (Public Library of Science, 2013)
Macrophage migration inhibitory factor (MIF) has important roles in supporting the proliferation and/or survival of murine neural stem/progenitor cells (NSPCs), but downstream effectors remain unknown. We show here that MIF robustly increases the expression of Sox6 in NSPCs in vitro. During neural development, Sox6 is expressed in the ventricular zone of the ganglionic eminence (GE) of mouse brains at embryonic day 14.5 (E14.5), cultured NSPCs from E14.5 GE, and NSPCs in the subventricular zone (SVZ) around the lateral ventricle (LV) of the adult mouse forebrain. Retroviral overexpression of Sox6 in NSPCs increases the number of primary and secondary neurospheres and inhibits cell differentiation. This effect is accompanied with increased expression of Hes1 and Bcl-2 and Akt phosphorylation, thus suggesting a role for Sox6 in promoting cell survival and/or self-renewal ability. Constitutive activation of the transcription factor Stat3 results in up-regulation of Sox6 expression and chromatin immunoprecipitation analysis showed that MIF increases Stat3 binding to the Sox6 promoter in NSPCs, indicating that Stat3 stimulates Sox6 expression downstream of MIF. Finally, the ability of MIF to increase the number of primary and secondary neurospheres is inhibited by Sox6 gene silencing. Collectively, our data identify Sox6 as an important downstream effector of MIF signaling in stemness maintenance of NSPCs.